The effect of brain vitalization exercise on muscle strength and endurance in people with dementia - Mustika Fitri; Ajeng Fauziyah; Hana Astria Nur (Jurnal Keolahragaan, 2021)
This study aims to determine the effect of brain vitalization exercise on muscle strength and endurance in people with dementia. The pre-experimental method with a one-group pretest-posttest design was used in this study. Purposive sampling technique was used in this study, then a sample of 31 people with dementia was obtained from a population of 78 people in Cibeunying Kidul District. The Arm Curl Test instrument is used in research that aims to measure arm muscle strength and Chair Stand Test which aims to measure leg muscle endurance. The data analysis technique in this study used Paired Sample T Test using the help of SPSS version 25 software. Based on data analysis, the results showed that the muscle strength obtained sig. 0.000 0.05 and on the durability of sig. 0.000 0.05 so it can be concluded that there is a significant effect of brain vitalization exercise on muscle strength and endurance in people with dementia.